Whither are the Tribals in Chhattisgarh…. Issue 1 (January 2013) - Saxena, Anupama; Ganveer, Dhammshil
According to the Census of India Report of 2011, majorihJ of the tribal population is concentrated in cwtral part of India coupled with overwhelming availabilihj of natural resources particularly in the state of Chhattisgarl! and Madhya Pradesh. These tribal people who are indigenous to India have remained backward, oppressed and exploited in terms of their political participation and socio-economic conditions compared to the general class in the sociehj, despite the constitutional safeguards and clusters of policies framed by the state and central government . This paper seeks to provide a review of the stahls of Tribals in Chhattisgarh state. Statistical comparison on various socio-economic indicators, with the parent state Madhya Pradesh have also been made .